Prospective study on a new combination of pulsed radiofrequency and platelet-rich plasma injections for managing grade I lumbosacral spondylolisthesis - Viet-Thang Le; Dung Tuan Hoang Bui; Phuoc Trong Do (Scientific Reports)
Abstract Our study aimed to investigate the clinical benefits of combining pulsed radiofrequency (PRF) and platelet-rich plasma (PRP) techniques for treating chronic lumbosacral radicular (CLSR) pain resulting from grade I spondylolisthesis (G1SL). Ninety-six patients with CLSR pain between March 2021 and March 2023 were included in this study, 58 patients with G1SL without instability on dynamic radiographs – Group A and 38 patients with instability – Group B. Pre-procedure, Group B had higher pain levels than Group A. Post-procedure and at follow-up intervals, Visual Analog Scale (VAS) pain scores improved in both groups (p < 0.05) and there were no significant differences between the groups. Both groups also showed significant improvement in ODI scores post-procedure, which was maintained at follow-up intervals. The treatment effect, evaluated using the modified MacNab criteria, showed high rates of excellent and good outcomes in both groups, with no significant differences. Importantly, no patients experienced severe complications or required open surgery during the 6-month follow-up. Based on these findings, a new treatment combining PRF and PRP applications appears beneficial in managing pain in regenerative medicine. So, further clinical studies are necessary to support and validate our preliminary findings.